Multifactorial Analysis of Work Accidents among Transportation Sector Workers in Parepare City - Russeng, Syamsiar S.; Saleh, Lalu Muhammad; Syafitri, Nurul Mawaddah; Imran, Naufal Hilmy; Nurazizah, Auliya; Nurhidayah, Andi Fatimah Mustovia (Media Kesehatan Masyarakat Indonesia, 2023)
Reports have shown that there has been a continuous annual increase in the number of traffic accidents in Indonesia. Parepare City, in particular, faces significant congestion in its public transportation system, leading to 167 cases and 144 cases of accidents in 2019 and 2020, respectively. Therefore, this study aims to analyze the influence of knowledge, attitude, personality, and safety riding practice on traffic accidents among transportation workers in Parepare City. This cross-sectional study comprised 100 respondents selected using the simple random sampling method. The study instrument was a questionnaire, which had previously been tested for its validity and reliability. The data obtained were analyzed using univariate analysis to describe the characteristics of each variable. In contrast, bivariate analysis was conducted using the chi-square test with a confidence level of 95%. Data were collected through interviews with a questionnaire and analyzed using multiple logistic regression with the forward LR method. The results showed that attitude and safety riding practice had a significant influence. Multivariate analysis showed that factors influencing accidents included attitude (AOR = 0.031; 95%CI = 0.45-0.26), practice (AOR = 0.108; 95%CI = 0.03-0.38), and knowledge (AOR = 0.337; 95%CI = 0.13-0.88), while personality had no effect. Based on the results, future studies were advised to conduct long-term investigations (longitudinal studies) to monitor changes in the variables observed and the relationship with the rate of traffic accidents.